ASSESSMENT SYSTEM OF PROCESS ACTIVITY OF STUDENTS IN PRACTICAL LESSONS IN PHYSICAL CULTURE AND SPORT - Boldov, A.S.; Karpov, V.Yu.; Alenurov, E.A.; Skorosov, K.K. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to substantiate the system for evaluating the effectiveness of students' process activities in the framework of practical classes in physical culture and sports. Methods and structure of the study. In the analytical study, methods of analysis and synthesis, generalization and modeling, and the axiomatic-inductive method were used. Results and conclusions. The authors have developed criteria for the process activity of university students in mastering the disciplines of the physical culture and sports block, taking into account inclusion, not only as achievement evaluation determinants of individual semesters, but also in the dynamic development of target performance.